PEDAGOGICAL PROBLEMS OF TRAINING ON THE BASIS OF MODERNIZATION OF EDUCATION. (Conference Zone, 2021)
The process of "modernization" in all spheres of society also applies to the educational process. In particular, the reform of the assessment of students' knowledge in accordance with modern requirements is a requirement of the times. are crucial normative documents to ensure the quality and efficiency of implementation in the process.